Sectoral Economic Mapping and Structural Transformation in the BASAJAN Corridor: A Spatial Policy Matrix Approach - Andri Suriansyah; Suriani Suriani; M. Shabri Abd. Majid (Graha Primera Saintifika, 2026)
Post-pandemic fiscal constraints within the BASAJAN (Banda Aceh, Sabang, and Jantho, Aceh Besar) economic corridor require precise, evidence-based policies to prevent inefficient public investment. This study maps sectoral economic structures and structural transformation to develop a spatial policy matrix for identifying priority sectors. Using constant-price Gross Regional Domestic Product (GRDP) data for the period 2019–2024 across 17 economic sectors, the study integrates the Location Quotient (LQ) and Sectoral Klassen Typology analyses. This approach produces a four-quadrant policy matrix comprising Prime Mainstay, Sustaining Mainstay, Potential, and Lagging Sectors. The empirical findings reveal a highly complementary spatial division of labor across the corridor. Banda Aceh functions as the primary tertiary agglomeration center for services and finance, Sabang exhibits strong specialization in maritime tourism, and Aceh Besar serves as the principal hinterland supporting food security and manufacturing. The findings indicate that a uniform development strategy across the BASAJAN corridor is unlikely to be effective. Therefore, local planning agencies (Bappeda) should prioritize fiscal allocations toward their respective Prime Mainstay Sectors. Furthermore, greater integration of Regional Spatial Planning (RTRW) across jurisdictions is essential to strengthen interconnected regional supply chains within the BASAJAN corridor.